Carbon Dots with Intrinsic Theranostic Properties for Bioimaging, Red‐Light‐Triggered Photodynamic/Photothermal Simultaneous Therapy In Vitro and In Vivo. Issue 6 (23rd December 2015) - Ge, Jiechao; Jia, Qingyan; Liu, Weimin; Lan, Minhuan; Zhou, Bingjiang; Guo, Liang; Zhou, Hangyue; Zhang, Hongyan; Wang, Ying; Gu, Ying; Meng, Xiangmin; Wang, Pengfei
Abstract : Cancer nanotheranostics combining therapeutic and imaging functions within a single nanoplatform are extremely important for nanomedicine. In this study, carbon dots (C‐dots) with intrinsic theranostic properties are prepared by using polythiophene benzoic acid as carbon source. The obtained C‐dots absorb light in the range of 400–700 nm and emit bright fluorescence in the red region (peaking from 640 to 680 nm at different excitations). More importantly, the obtained C‐dots exhibit dual photodynamic and photothermal effects under 635 nm laser irradiation with a singlet oxygen ( 1 O2 ) generating efficiency of 27% and high photothermal conversion efficiency of 36.2%. These unique properties enable C‐dots to act as a red‐light‐triggered theranostic agent for imaging‐guided photodynamic–photothermal simultaneous therapy in vitro and in vivo within the therapeutic window (600–1000 nm). Abstract : Carbon‐dots (C‐dots) with intrinsic theranostic properties are successfully synthesized by using polythiophene benzoic acid (PBA) as the precursor. The red fluorescence with robust antibleaching and efficient red‐light‐triggered generation of heat and 1 O2 are key properties that enable C‐dots to act as cancer theranostic for imaging‐guided, photodynamic–photothermal simultaneous therapy.